Effect of 16 Weeks Walking With Different Dosages on Psychosocial Function Related Quality of Life Among 60 to 75 Years Old Men - Elham Karimi Torghabeh; Mohammad Ehsani; Hashem Koozechian; Yadollah Mehrabi (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: The purpose of current semi-experimental study was a survey on effect Abstract  of 16 week walking on psychosocial functioning related to quality of life among 60 to 75 years old men. Methods & Materials: For this reason, short form of health-related quality of life questionnaire (SF-36) and Geriatric Depression Scale (GDS) had been distributed to the subjects at 2 times of pre-test and posttest. Statistical sample of current study was 60 to 75 years old men who placed at Kahrizak house and assessed by considering physically and medical background. Also factors of entrance to the intervention like age range, satisfaction and intention to participate in walking program, no history of diabetic, cardiovascular, Parkinsonism diseases and postural, neurological, musculoskeletal disorders, lack of having clinical background like visual disorders or disordering on equilibrium system, lack of motor limitation, foot print disorders, having surgery and mental health had been determined and assessed. Finally after primary studies, 80 person selected and categorized accidentally to the 3 experimental group (1, 2, 3 sessions per week, 30 min walking with moderate intension at every sessions) and one control group (without physical activity in period of 16 week). Data analyzed by employing ANOVA, Pearson coefficient and scheffe post-hoc tests at the significance level of P<0.05. Results: Results showed that psychosocial functioning of men with 60 to 75 years old increase by influence of 16 week walking and increase of exercise sessions lead to more effectiveness of walking. Also there was no significant different between psychosocial functioning of subjects within 1 session and 3 sessions experimental groups (P>0.05). Conclusion: On the basis of results, we can say that doing regular walking with efficient and standard dosage for elderly people, can increase their quality of life. Furthermore designing and action operating regular walking program for elderly men on the basis of special, logical and systematic pattern under the supervision of aware coaches have been recommended on the basis of results.